Multimarket Maneuvering in Uncertain Spheres of Influence: Resource Diversion Strategies - McGrath, Rita Gunther; Chen, Ming‐Jer; MacMillan, Ian C. (Academy of Management Review, 1998)
Rita Gunther McGrath, Ming-Jer Chen, Ian C. MacMillan, Multimarket Maneuvering in Uncertain Spheres of Influence: Resource Diversion Strategies, The Academy of Management Review, Vol. 23, No. 4 (Oct., 1998), pp. 724-740